2002
DOI: 10.1086/338813
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Bloodstream Infections among Human Immunodeficiency Virus-Infected Patients: Incidence and Risk Factors

Abstract: To assess the incidence of nosocomial bloodstream infections (NBSIs) in human immunodeficiency virus (HIV)-infected patients, and to analyze the main associated risk factors, we performed a 1-year multicenter prospective study of patients with advanced HIV infection who were consecutively admitted to 17 Italian infectious diseases wards. As of May 1999, a total of 65 NBSIs (4.7%) occurred in 1379 admissions, for an incidence of 2.45 NBSIs per 1000 patient-days. Twenty-nine NBSIs were catheter-related bloodstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 49 publications
(62 reference statements)
4
39
1
Order By: Relevance
“…Confirming earlier reports (Bassetti et al 2007;Blumberg et al 2001;Bross et al 1989;Sung et al 2001;Wey et al 1989), our study showed that renal insufficiency was independently related to candidaemia in the logistic regression model. Our study did not find other significant host-related factors, which is in contrast to other studies that reported diabetes mellitus (Michalopoulos et al 2003;Wu et al 2014), HIV infection (Chowta et al 2007;Petrosillo et al 2002), malignancy (Zaoutis et al 2010) and prematurity (Saiman et al 2000;Wu et al 2013), as significant risk factors. This could possibly due to several factors -our small sample size, particularly for HIV infection and prematurity; different study population by Zaoutis et al (2010) who included only paediatric patients and diabetes mellitus being too prevalent in our population that it is present too often in both groups.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Confirming earlier reports (Bassetti et al 2007;Blumberg et al 2001;Bross et al 1989;Sung et al 2001;Wey et al 1989), our study showed that renal insufficiency was independently related to candidaemia in the logistic regression model. Our study did not find other significant host-related factors, which is in contrast to other studies that reported diabetes mellitus (Michalopoulos et al 2003;Wu et al 2014), HIV infection (Chowta et al 2007;Petrosillo et al 2002), malignancy (Zaoutis et al 2010) and prematurity (Saiman et al 2000;Wu et al 2013), as significant risk factors. This could possibly due to several factors -our small sample size, particularly for HIV infection and prematurity; different study population by Zaoutis et al (2010) who included only paediatric patients and diabetes mellitus being too prevalent in our population that it is present too often in both groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies reported that central venous catheterization (Bassetti et al 2007;Petrosillo et al 2002;Wu et al 2013), prolonged hospital stay (Bassetti et al 2007;Petrosillo et al 2002), ICU stay (Amrutkar et al 2006), mechanical ventilation (Saiman et al 2000), surgery (Blumberg et al 2001;Playford et al 2008;Wu et al 2013) and total parenteral nutrition (Amrutkar et al 2006;Bassetti et al 2007;Blumberg et al 2001) were significant risk factors for candidaemia. However, our study found that these risk factors were only significant in bivariate analysis but were insignificant after multivariate logistic regression analysis; indicating that although these factors were more commonly found among patients with candidaemia that those without, statistically they were not considered significant independent risk factors for candidaemia in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Petrosillo and colleagues showed an almost-4-fold increase in mortality between disease-matched HIV-positive patients with BSIs and those without BSIs (24.6% versus 7.4%) (256).…”
Section: At-risk Patient Populationsmentioning
confidence: 98%
“…Several IDUs use the central venous catheter during hospitalization to inject street drugs, which are often contaminated, thus further increasing the risk of catheter infection, which is already higher in this population because of the higher S. aureus colonization rate, of preexistent pathologies of the veins (thrombophlebitis, etc. ), of the difficult line insertion, and of the frequent use of central venous catheters for drawing of blood samples from these patients [27]. A recent prospective study analyzing 1,379 hospital admissions in Italy confirmed that, at least in HIV-infected patients, active injection drug use is independently associated with nosocomial bloodstream infections [27].…”
Section: Nosocomial S Aureus Infections and Idusmentioning
confidence: 99%
“…), of the difficult line insertion, and of the frequent use of central venous catheters for drawing of blood samples from these patients [27]. A recent prospective study analyzing 1,379 hospital admissions in Italy confirmed that, at least in HIV-infected patients, active injection drug use is independently associated with nosocomial bloodstream infections [27]. The most common pathogen associated with bacteremia in this study was S. aureus (29.8% of all nosocomial bloodstream infections and 32.3% of all catheter-related bloodstream infections).…”
Section: Nosocomial S Aureus Infections and Idusmentioning
confidence: 99%